Penerapan Metode Drill Sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik Kelas I Pada Tema Kegemaranku Di SDN 99/IX Danau Kedap - Nurjanah Nurjanah (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2020)
The purpose of this class action research is to reveal data, information and discuss about the application of the Training Method (Drill) as an effort to improve the learning outcomes of Class I students at SDN 99 / IX Danau Kedap on the theme of my first semester Semester I in 2019/2020 Academic Year. This type of research is a classroom action research (CAR) of two cycles. This study consisted of two cycles, each cycle consisting of two meetings, following 4 stages: planning, implementing, observing and reflecting. The subjects of this research were Class I students at SDN 99 / IX Danau Kedap, amounting to 13 students. Data collection was carried out through observation, daily journals (daily notes), learning achievement tests and documentation. The data obtained are quantitative descriptive with percentage calculations and data reduction. The conclusion of this study the drill method has a significant impact on the learning outcomes of Class I SDN 99 / IX students in Danau Kedap through the act of giving praise.